Wahrscheinlichkeitsvergleich und inferenzstatistisches Schließen: Fähigkeiten von Kindern des 4. und 6. Schuljahrs bei Basisproblemen aus dem Bereich Daten und Zufall (mathematica didactica, 2014)
Mathematical instruction should foster the cumulative acquisition of abilities in the field of data and chance from the early years in elementary school on. However, the knowledge about abilities of students in elementary grades is still deficient. This article focusses on the abilities to handle two basic problems dealing with the comparison of probabilities and inferential reasoning. The results show that children in grade 4 and 6 are already able to solve these problems if they are posed as special, age-adequate problems. However, typical strategies and (mis-)conceptions can also be identified. This article includes a detailed description of the problems used and discusses instructional implications of the study.